(untitled) (Research, Society and Development, 2022)
This work aims to epidemiologically analyze the evolution of schistosomiasis cases in the State of Sergipe, based on secondary data from the Information System of the Schistosomiasis Surveillance and Control Program (SISPCE), made available by the State Department of Health. A retrospective and descriptive study with a quantitative approach was performed which analyzed the secondary data obtained by the Schistosomiasis Control Program System (SISPCE), together with the State Health Department of the State of Sergipe, from 2011 to 2021. It was evident that in the last 10 years there was a decrease in the adherence of municipalities to the PCE and this generated a lower number of schistosomiasis diagnoses. Since early diagnosis allows for rapid treatment, ends the cycle of Schistosoma mansoni and helps prevent severe cases, state incentives for municipal adherence could help prevent the spread of this disease.